Behavioral Characteristics of Gout Patients and Their Impact on the Results of Urate Lowering Therapy - J. Chen; P. Zhou; W. Tan; M. Zheng; N. Y. Oshmianska (Acta Biomedica Scientifica)
Background. Gout is frequently accompanied by hypertension, obesity, and/or impaired glucose tolerance, which are often complicated with heavy smoking and dietary violations, especially in male patients.Objective. To determine the behavioral characteristics of gout patients that could impact the results of urate lowering therapy.Subjects and methods. The relationship between behavioral characteristics and results of urate lowering therapy were investigated in 74 male gout patients of Chengdu Rheumatism Hospital. The results of treatment were evaluated using serum uric acid contents before and after treatment, VAS pain score before and after treatment. Behavioral characteristics for the last ten years (smoking status, daily volume of drinking water, etc.) were accessed by means of retrospective survey.Results. In gout patients with poor treatment response, serum uric acid at the beginning of the treatment was already significantly lower (365.76 ± 163.06 μmol/L); this trend was also noted in a “slow progress” group, while patients with higher serum uric acid before treatment had notably better response to urate lowering therapy. During further analysis age negatively correlated with serum uric acid (r = –0.328; p = 0.002) and uric acid clearance ratio (r = –0.299; p = 0.002).In patients with uric acid clearance ratio above 40 % the prevalence of kidney diseases (stones or dysfunction) was significantly lower compared to other groups. There was no significant influence of hypertension, diabetes mellitus, fatty liver or hyperlipidaemia on uric acid clearance ratio (p > 0.05).Amount of drinking water also influenced the serum uric acid clearance ratio. Bigger amount of patients in the “fast progress” group (40.0 % compared to 30.44 and 25.0 %) tended to drink more water.Conclusion. In most gout patients, serum uric acid levels before treatment acted as the reliable predictor of good response to urate lowering therapy. Treatment response (serum uric acid clearance ratio) correlated positively with the hyperuricemia and drinking sufficient amounts of water, negatively – with prolonged smoking (more than 10 years) and age.